Antibiotic resistance profile of Coagulase-negative staphylococci species isolated from subclinical mastitis in Colombian dairy herds - Vargas-Abella, Julio César (2024)
Boyacá is Colombia's fifth-largest milk-producing department. Previous studies have shown the importance of Coagulase-negative Staphylococci (CNS) species as causes of subclinical mastitis in dairy herds. This work aimed to determine the antibiotic resistance profile in CNS obtained from subclinical mastitis, and the presence of the mecA gene. CNS DNA was taken from a previous study of the research group, and specific primers were used for the detection of the mecA gene in isolates that showed antibacterial resistance to at least one of the following antibiotics: ampicillin, tetracycline, streptomycin, oxacillin, penicillin, and enrofloxacin. The results show different patterns of antibiotic resistance in the CNS isolates despite being obtained from the same herd. In addition, S. chromogenes and S. epidermidis were the most prevalent pathogens, and with the highest presence of the mecA gene (33.4 and 37.5% respectively). The results are like those found in other countries and worldwide studies, however, the presence of the mecA gene was not associated in some species such as S. capitis, S. sciuri, and S. haemolyticus with phenotypic resistance to oxacillin or penicillin, therefore, more research is required on other genes possibly associated with this.